2011
DOI: 10.1136/jnis.2010.004564
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and effectiveness of inferior vena cava filters in patients with stroke

Abstract: IVC filters have an acceptable safety profile in stroke patients. In our cohort, they were effective in preventing life-threatening PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In a seven-year retrospective study by Somarouthu et al, results showed that IVC filter placement in stroke patients resulted in imaging confirmed PE at a frequency of 4% and post-filter imaging confirmed DVT occurred in 14% of patients. They concluded that IVC filters have an adequate safety profile and are efficient in preventing fatal PE in patients with stroke [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a seven-year retrospective study by Somarouthu et al, results showed that IVC filter placement in stroke patients resulted in imaging confirmed PE at a frequency of 4% and post-filter imaging confirmed DVT occurred in 14% of patients. They concluded that IVC filters have an adequate safety profile and are efficient in preventing fatal PE in patients with stroke [20].…”
Section: Discussionmentioning
confidence: 99%
“…Certain patients, such as spinal cord injury patients and stroke patients, remain at high risk of VTE that is due to immobility, and permanent IVC filters may therefore be considered in these patients. IVC filters have been found to be safe in patients with nonhemorrhagic stroke, and certain authors have advocated for prophylactic filter placement in stroke patients; however, no guidelines currently advocate for prophylactic filter placement in stroke [65].…”
Section: Prophylacticmentioning
confidence: 99%
“…However, once a PE or symptomatic DVT is diagnosed in patients with ischaemic stroke, full therapeutic anticoagulation is recommended [50]. In patients with an intracerebral haemorrhage, a vena cava filter might be an alternative [53], but this also requires anticoagulation in the longer term.…”
Section: Acute Stroke Carementioning
confidence: 99%